Influence of buckwheat malt on beer properties - Parkhomenko, Anastasia; Mukoid, Roman (My University, 2020)
The prospects of using buckwheat malt for the production of low-gluten beer are shown. Gluten is absent in such cereals as buckwheat and rice, and in other cereals the amount of gluten is: corn 80 ppm, barley 151 ppm, wheat 162 ppm. Therefore, for the preparation of low-gluten beer buckwheat malt and barley malt are recommended

Показано перспективність використання гречаного солоду для виробництва низькоглютенового пива. Клейковина відсутня в таких крупах, як гречка і рис, а в інших крупах кількість клейковини становить: кукурудза 80 ppm, ячмінь 151 ppm, пшениця 162 ppm. Тому для приготування пива з низьким вмістом клейковини рекомендується використовувати солод гречаний і ячмінний
Keywords: кафедра біотехнології продуктів бродіння і виноробства; ячмінь; пиво; гречка; клейковина; солод; сусло; barley; beer; buckwheat; gluten; malt; wort